Pelayanan Pastoral Dalam Meningkatkan Keharmonisan Keluarga Yang Mengalami Konflik - Juliono (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2024)
Research Objective: This study aims to examine the crucial role of pastoral care in fostering family harmony in the face of conflict. Approach and Research Methods: This research employs literature analysis and case studies to identify the factors causing family conflicts, including poor communication, economic issues, and infidelity. Research Findings: The results of the case studies demonstrate the effectiveness of pastoral care in addressing various conflict situations, such as relationship recovery after infidelity and financial support. Conclusion: This study recommends ongoing training for pastors, collaboration with other professionals, and proactive approaches to enhance the effectiveness of pastoral care in building harmonious families.